DNase I alleviates renal inflammatory injury in MRL/lpr mice by inhibiting NETs formation - Zhang, Manling; Xie, Xinran; Da, Gula; Li, Hongbin; Jin, Yong (Frontiers in Immunology, 2025)
BackgroundLupus nephritis (LN) is one of the most common complications of systemic lupus erythematosus (SLE) and represents a frequent and potentially life-threatening clinical condition. The pathogenesis of LN involves multiple immune cell types. Notably, neutrophil extracellular traps (NETs) formation has been closely associated with renal inflammatory injury. However, the underlying pathophysiological mechanisms remain incompletely understood.MethodsWe administered DNase I to MRL/lpr mice, monitored signs and renal pathology, quantified gene expression levels, and conducted flow cytometry and RNA-seq analysis. The expression levels of NETs molecular markers and key genes involved in relevant molecular pathways were assessed in both an in vitro cell model treated with PMA and DNase I, as well as in peripheral blood neutrophils from SLE patients, followed by correlation analysis.ResultsFollowing DNase I treatment, the lupus-related manifestations, renal pathology, and renal function were significantly improved in the LN mouse model. The expression levels of MPO and CitH3 were reduced, and the expression of inflammatory damage molecules, including IL-1β, TNF-α, and Kim1, was down-regulated. RNA-seq analysis revealed that the neutrophil and T cell activation and chemotaxis pathways were suppressed, and the infiltration of cytotoxic immune cells in the kidneys was decreased in the DNase I-treated group compared to MRL/lpr mice. In an in vitro model of PMA-induced neutrophil activation, the addition of DNase I inhibited the expression of MPO and CitH3 and down-regulated the expression of inflammatory signaling molecules (TLR4, MYD88, and HMGB1), chemotactic molecule CCL2, and the key molecule of NETs formation, PADI4. Furthermore, the critical molecules PADI4, HMGB1, TLR4, and MYD88 were significantly upregulated in peripheral blood neutrophils from LN patients, and their expression levels in the kidneys of MRL/lpr mice increased in a time-dependent manner.ConclusionsDNase I alleviates renal inflammatory injury by inhibiting the NETs/TLR4/MYD88 cell signaling axis, reducing the formation of NETs and the infiltration of immune inflammatory cells such as T cells and macrophages. These findings may provide a novel clinical prevention and treatment strategy for LN.